PASAR UANG SYARIAH DALAM MENSUKSESKAN MEA - Hasibuan, Abdul (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Goals to be achieved in the activities of Islamic Money Market article in the success of the MEA where the money market is a target for the smooth running of the business and to grow the business in a free market program MEA. In this paper the author focuses on money market instruments as money market shari'a is an Islamic banking facilities and financial institutions. With literature study authors apply the main source of this article, regarding various provisions of studies that have been done before, and is supported by a study published by various institutions in the form of journals and other scientific studies. The results of this paper are financial markets can be concluded that the business made easy by the financial markets that led to trade foreign exchange and capital flow running smoothly between countries or companies. Without the financial markets, the borrower money (creditors) will have difficulty in finding debtors who are willing to lend to him.